2012
DOI: 10.4314/sajas.v42i3.5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of butyric acid supplementation and whole wheat inclusion on the performance and carcass traits of broilers

Abstract: To evaluate the effects of butyric acid (BA) levels and wheat form (WF) on the performance of broiler chickens, 320 day-old Ross 308 broiler chicks were randomly distributed among 32 floor pens. A 4 × 2 factorial arrangement with four levels of BA (B 1 : 0 g BA/kg in both starter and grower feed; B 2 : 2.5 g BA/kg in both starter and grower feed; B 3 : 2.5 g BA/kg in starter and 1 g BA/kg in grower feed; and B 4 : 2.5 g BA/kg in starter and 0 g BA/kg in grower feed) and two forms of wheat (whole (WW) vs. groun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 26 publications
1
16
1
Order By: Relevance
“…It is certain, however, that limited direct exposure to the diets may have occurred when pups began to eat their dam's diet as they approached weaning [47]. Increased consumption of dietary fibres and production of butyric acid [48] are associated with increased intestinal length [49] and increased mineral absorption [50][51][52][53] as observed in this study by increased calcium concentration in the pups femur at weaning. The effects on colon length are usually accompanied by an increase in weight and crypt size [54][55][56] which was not observed in the present study.…”
Section: Discussionmentioning
confidence: 65%
“…It is certain, however, that limited direct exposure to the diets may have occurred when pups began to eat their dam's diet as they approached weaning [47]. Increased consumption of dietary fibres and production of butyric acid [48] are associated with increased intestinal length [49] and increased mineral absorption [50][51][52][53] as observed in this study by increased calcium concentration in the pups femur at weaning. The effects on colon length are usually accompanied by an increase in weight and crypt size [54][55][56] which was not observed in the present study.…”
Section: Discussionmentioning
confidence: 65%
“…It is postulated that excessive amounts of dietary citric acid inclusion may compromise performance because two experiments using 60 g/kg citric acid in diets reported significant decreases in body weight gain. (Patten and Waldroup, 1988;Alçiçek et al, 2004;Leeson et al, 2005;Gunal et al, 2006;Hernández et al, 2006;García et al, 2007;Paul et al, 2007;Biggs and Parsons, 2008;Pirgozliev et al, 2008;Samanta et al, 2008;Al-Kassi and Mohssen, 2009;Ao et al, 2009;Bozkurt et al, 2009;Chowdhury et al, 2009;Kim et al, 2009;Mahdavi and Torki 2009;Panda et al, 2009a,b;Haque et al, 2010;Nourmohammadi et al, 2010;Smulikowska et al, 2010;Esmaeilipour et al, 2011;SalgadoTránsito et al, 2011;Aghazadeh and Tahayazdi, 2012;Nourmohammadi et al, 2012;Świątkiewicz and Arczewska-Wlosek, 2012). 2 Detailed information for each organic acid was provided in the Tables 5 through 9.…”
Section: Citric Acidmentioning
confidence: 99%
“…No clear explanation for this anorexic effect has been postulated. In addition, high inclusion levels of butyric acid may have a negative effect on feed efficiency because Aghazadeh and TahaYazdi (2012) reported that 25 g/kg of dietary butyric acid decreased feed efficiency by 1.0%. Based on the current data, however, it appears that butyric acid at low inclusion levels may have the most promising effects on broiler performance among dietary organic acids.…”
Section: Butyric Acidmentioning
confidence: 99%
“…In addition, butyrate of stimulates cell growth and differentiation of normal cells and apoptosis (early cell death) of tumour cells which represents'butyrate paradox' (Canani et al, 2011).Previous studies showed increased jejunum villi height (Adil et al, 2010;Jerzsele et al, 2012;Chamba et al, 2014), villi height to crypt depth ratio (Hu and Guo, 2007;Shahir et al, 2013) and comparable crypt depth (Hu and Guo, 2007;Adil et al, 2010;Smulikowska et al, 2009;Chamba et al, 2014;Sayrafi et al, 2011;Antongiovanni et al, 2007) by supplementation of different forms of butyric acid. Lakshmi and Sunder (2015) 0.25 Liver weight + Aghazadeh and Yazdi (2012) It is clear from the Table 4 that inclusion of BA in broiler diet improves the weight of carcass indicating anabolic effect in broiler chicken.…”
Section: Antioxidant Effectmentioning
confidence: 99%
“…Addition of 0.6 (Panda et al, 2009), 0.3 % BA (Lakshmi and Sunder, 2015) in broiler chicken reduced the abdominal fat. While, it was not influenced by inclusion of 0.04 % microencapsulated SB (Zhang et al, 2011b), 0.3 % protected BA (Mahdavi andTorki, 2009), 0.25 (Aghazadeh andYazdi, 2012) and 0.2 % BAG ( Jang, 2011).…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 99%